Ensino de arte e ruralidade: reflexões e apontamentos interculturais. - Naghettini, Sergio (2018)
This master’s degree dissertation in Arts presents a research developed at Uberlândia Federal University. Its overall aim was to apprehend and reflect on art planning and teaching for rural areas students in order to support teaching and learning process in association with interculturality. Its specific aims included: to grasp strategies and educational proposals to substantiate, address, know and perceive the interaction of different cultures permeating the student’s schooling space in the rural area of Uberlândia municipality; to analyze theoretical- methodological dimensions related to the so-called Triangular Approach for art teaching in the conception and practicing of a teaching focused on art and culture for rural pupils; to think of expectations, difficulties, achievements and realities concerning teaching practice with a focus on art and culture for rural students. The research starting point refers to the following questions: does art teacher discuss, know and recognize the culture do fundamental level students attending rural school and establish plural relations regarding culture? How can he/she make his/her own lessons meaningful for the formation of student cultural identity in the process of seeking creative possibilities to work on local culture and aesthetics? How can he/she come to discuss local/rural culture and perceive thoughtfully the setting in which they live and have significance for the students? What facts and thought originating from this practice help it to be meaningful and renews its meaning? Building answers to such inquiries required a research unfolded as a case study focusing on the teaching practice of art education. As a way of presenting results, the methodology of triangulating procedures was adopted in light of the qualitative approach, ethnographic research and the phenomenological method, as in a typical observation of those who research their own professional practice. Theoretical and conceptual bases of the research were drawn from authors such as Dewey (1958), Bondía (2002), Barbosa (1998a) and Arroyo (2002). The cultural diversity of the students in classroom led to thoughtful moments and artistic actions involving works that integrate art and culture relaying on Triangular Approach to help students develop the ability to represent, interpret, imagine and understand themselves and the intercultural relations. This perspective of educational practice for rural school seeks to relate the education process with its audience (students from 6th to 9th year of elementary school), integrating intercultural relations and pupils in Art classes. Finally, the contact with different cultures made art teaching practice in the school focused in the research a moment of discovery, of building knowledge and concepts for an aesthetic of the daily life in parallel to the observation of regional cultures; in addition, it helped the debate on new conceptions of art teaching practice in a pedagogy that integrates art with culture and ruralness.